Does Expectation Influence Relationship? An Investigation of Parental Expectation and Parent-Child Relationship Among Selected Chinese Groups - Chiang, Sharon H.C.; Ellis, Arthur K. (International Dialogues on Education Journal, 2019)
Family is the primary learning environment for children. Parents are children’s first social network. Prior to and concurrent with school education, the critical influence of parental expectation eventually permeates into all aspects of an individual’s life. However, the subject of family relationships is rarely addressed within school curricula. Furthermore, due to some seemingly unreachable parental expectations and unbearable family discord, brokenness continues to increase. The influence of expectation on relations is an area of limited academic research. This study explores parental expectation and its influence on parent-child relationships, using mixed methods: qualitative research methods involving interviews and focus group studies; and quantitative research utilizing a 41 item Likert scale questionnaire which was analyzed using exploratory factor analysis (EFA) in order to identify underlying relationships among measured variables. This exploratory study establishes the basis to encourage further research on the topic of expectations and relationships.